Preparation and Characterization of the Dichloro bis-(2-Pentyne) Complex [WCl2(CO)(NCMe)(η2-EtC2Me)2] - Al-Jahdali, Mutlaq (Asian Journal of Chemistry, 2016)
Preparation of [WCl2(CO)3(NCMe)2] by reacting of [WI2(CO)3(NCMe)2] with two equivalents of NaCl in acetone, followed with an excess of EtC2Me (2-pentyne) in CH2Cl2 gives the 2-pentynecomplex [WCl2(CO)(NCMe)(η2-EtC2Me)2] (1). Equimolar quantities of 1 with (L = NPh3 and PPh3) react in CH2Cl2 to give the acetonitrile replaced products, [WCl2(CO)(PPh3)(η2-EtC2Me)2] (2) and [WCl2(CO)(NPh3)(η2-EtC2Me)2] (3) in good yield. Reaction of 1 with equimolar amount of bidentate of {L2 = Ph2P(CH2)nPPh2 (n = 1-5)} in CH2Cl2 at room temperature afforded the mono-(2-Pentyne) complexes, [WCl2(CO)(Ph2P(CH2)nPPh2) (η2-EtC2Me)] ( n = 1-5) (4-8).